Child Abuse, Exploitation and the Quest for a Better Life in Sefi Atta’s Everything Good Will Come (2004) and Swallow (2010) and Toni Morrison’s The Bluest Eye (1970) - Babacar Diakhaté (Britain International for Academic Research (BIAR) Publisher, 2020)
This Article brings to light the topicality of the 21st century African and African-American female novel especially in Sefi Atta’s Everything Good Will Come and Swallow, and Toni Morrison’s The Bluest Eye. As the African traditional societies have much progressed, this work aims at showing that the African and African-American female novel has also progressed thematically speaking. It addreses new literary trends like Adoption, Rape, Incest, Child Abuse, Emigration and Identity Issues.